Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kota Payakumbuh - Ferdawati; Elina Febrianti; Reni Endang Sulastri; Welsi Haslina; Syafira Ramadhea Jr (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2023)
Motor vehicle tax is part of the local tax that contributes greatly to regional income in the city of Payakumbuh. Taxpayer compliance in paying taxes will be able to increase tax revenues so that regional income for development also increases. This study aims to obtain empirical evidence regarding the elements that can affect the compliance of motor vehicle taxpayers in paying their obligations. The variables that are the focus of this study are the influence of taxpayer awareness, sanctions, service quality and tax socialization on motor vehicle taxpayer compliance in Payakumbuh. This study took the population of motorized vehicle taxpayers who were recorded in SAMSAT Payakumbuh city by determining the sample using simple random sampling method. Data were collected by distributing questionnaires and the data analysis technique used multiple linear regression analysis. From this study, it was found that three elements, namely taxpayer awareness, tax service quality and tax socialization have an influence on taxpayer compliance in paying motor vehicle taxes in Payakumbuh, but for tax sanctions have no effect on taxpayer compliance in paying vehicle taxes. motorized in the city of Payakumbuh.